PEDAGOGICAL KNOWLEDGE IN THE CONTENT OF PEDAGOGICAL PREPARATION OF FUTURE TEACHERS - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2006)
The necessity of including of different pedagogic knowledge in the content of pedagogic training of students o f pedagogic university and its structuring on the base of different approached is proved.